How should job displacement wage losses be insured? - Donald O. Parsons (IZA World of Labor, 2018)
Job displacement represents a serious earnings risk to long-tenured workers through lower re-employment wages, and these losses may persist for many years. Moreover, this risk is often poorly insured, although not for a lack of policy interest. To reduce this risk, most countries mandate scheduled wage insurance (severance pay), and it is voluntarily provided in others. Actual-loss wage insurance is uncommon, although perceived difficulties may be overplayed. Both approaches offer the hope of greater consumption smoothing, with actual-loss plans carrying greater promise.
Keywords: J65; J63; 330; wage insurance; job displacement; severance pay